Model development in DNDC for the prediction of evapotranspiration and water use in temperate field cropping systems. (June 2016) - Dutta, B.; Smith, W.N.; Grant, B.B.; Pattey, E.; Desjardins, R.L.; Li, C.
Abstract: This paper integrates recent research to improve, test, and verify the process based DeNtrification DeComposition (DNDC) model to estimate evapotranspiration (ET) through a revised FAO Penman–Monteith approach. ET estimates along with biomass and soil water content for spring wheat and corn were improved and found to be in good agreement with the observations at three field sites in eastern Canada (Ottawa). The statistical evaluations (RMSE (mm day −1 ) and R 2 ) of ET for the newly revised model (0.88 and 0.76 for corn and 0.93 and 0.78 for wheat) showed improvements over DNDC93 (1.95 and 0.22 for corn and 1.62 and 0.09 for wheat) which used the Thornthwaite equation for estimating potential evapotranspiration. In addition, evaluations of water use efficiency for corn and wheat showed good agreement between observations and the modified model. The study demonstrates the inter-dependencies of ET with biomass production and soil/atmosphere water balance. Graphical abstract: Highlights: Improved evapotranspiration (ET) of process based model evaluated for field crops. Modified ET routine included FAO Penman–Monteith equation with crop specificity. Analysis of three versions of model statistically evaluated against measured ET. Improved model gave very comparable overall result to observed values with low bias. Predictions for soil water content and biomass also indicated no systemic bias.